2017
DOI: 10.1103/physrevapplied.7.034012
|View full text |Cite
|
Sign up to set email alerts
|

Improper Ferroelectricity in Stuffed Aluminate Sodalites for Pyroelectric Energy Harvesting

Abstract: Ferroelectricity in stuffed aluminate sodalites, (Ca1−xSrx)8[AlO2]12(WO4)2 (x ≤ 0.2) (C1−xSxAW), is demonstrated in the present study. Pyroelectric measurements clarified switchable spontaneous polarization in polycrystalline C1−xSxAW, whose polarization values were on the order of 10 −2 C/cm 2 at room temperature. A weak anomaly in the dielectric permittivity at temperatures near the ferroelectric transition temperature suggested improper ferroelectricity of C1−xSxAW for all investigated values of x. A compr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…This value is similar to previously reported values for improper ferroelectrics . Given the small P s and the weak dielectric anomaly discussed in the preceding paragraph, we concluded that CSAM‐16 is an improper ferroelectric material as in the case of (Ca 1 −x Sr x ) 8 [AlO 2 ] 12 (WO 4 ) 2 .…”
Section: Resultssupporting
confidence: 90%
“…This value is similar to previously reported values for improper ferroelectrics . Given the small P s and the weak dielectric anomaly discussed in the preceding paragraph, we concluded that CSAM‐16 is an improper ferroelectric material as in the case of (Ca 1 −x Sr x ) 8 [AlO 2 ] 12 (WO 4 ) 2 .…”
Section: Resultssupporting
confidence: 90%
“…This relationship provides a predictive guideline for estimating T C of a given material, which would complement the design approach based on group theory and first principles. Further, the findings open routes to the possible use of hybrid improper ferroelectrics in technological applications: for example, pyroelectric energy harvesting [83][84][85] , where the tunability of T C is advantageous for achieving a large electrothermal coupling factor.…”
Section: Discussionmentioning
confidence: 97%
“…All these materials perform better than conventional PZT‐5H (a type of soft PZT). The lead‐free compositions such as LiNbO 3 , CSBN (Ca 0.15 (Sr 0.5 Ba 0.5 ) 0.85 Nb 2 O 5 ), CSAW ((Ca 1− x Sr x ) 8 (AlO 2 ) 12 WO 4 ), and BTO based and BNT‐BTO based are not necessarily better than PZT for pyroelectric energy conversion, but they are better than conventional lead‐free counterparts, e.g., ZnO. PZT with aligned porosity proved to have a substantial increase in energy density compared to dense PZT .…”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%